The effect of generative design and topology optimization on the design and manufacturing of components in additive manufacturing - Omar Lkadi; Mohammed Nassraoui; Otmane Bouksour (Incertitudes et Fiabilité des Systèmes Multiphysiques)
Additive manufacturing, has shown great promises, offering unexpectable design freedom and manufacturing flexibility. but traditional design methodologies cannot fully exploit the functionality of am. this study explores the impact of generative design and topology optimization in the design and production of parts in additive production. by using these advanced design tools, we aim to optimize the case study performance, minimize material usage, and unlock design opportunities. The case study is a gripper arm which is part of a robot deputed to the handle meteors is presented to demonstrate the application of these methods. additionally, it offers a useful description of Autodesk’s generative design, a software, used in our case, that uses generative design to generate a series of potential solutions to a static structural design problem. the finding reveal how generative design and topology optimization can significantly enhance component performance, reduce mass, and enable complex geometries that are difficult or impossible when using traditional methods. additionally, the paper highlights the importance of taking manufacturability constraints into account during the design process.